Improvement of hydrogen storage characteristics of carbon nanostructural variants admixed nano MgH2 - Singh R.K.; Kumar R.; Raghubanshi H.; Srivastava O.N. (My University, 2025)
In the present work, we have synthesized and studied the catalytic effect of different carbon nanostructures (CNSs) on the absorption kinetics, decomposition temperature of MgH2. Ball-milling was used to reduce the particle size of MgH2 and CNS catalysts were used to enhance the hydrogen storage properties at lower temperatures. In particular, 2wt% twisted carbon nanofibres (TCNF) admixed ball-milled MgH2 (MgH2-2TCNF) corresponds to better hydrogenation/ dehydrogenation behaviour. The commencement of H-desorption temperature is ∼420 ?C for pure MgH2, ∼ 330 °C for TCNF admixed MgH2, which is further lowered to 297 °C for TCNF admixed ball-milled MgH2. Thus, desorption temperature gets more than 125 °C lower compared to commercial MgH2. After the desorption, Mg- 2TCNF (ballmilled) shows 5.03 wt% absorption as compared to 3.05 wt% for the ball milled MgH2 in the first 10 minutes even at 180 °C and an applied pressure of 2MPa. Whereas in the case of 2TCNF admixed MgH2 it shows absorption of 4.28 wt% at a higher temperature 300 °C and an applied pressure of 2 MPa. The improved properties originate due to the CNSs catalyst and nanostructure of MgH2 introduced during ball milling in hydrogen pressure. Copyright © (2014) by the Committee of WHEC2014 All rights reserved.